Removal of dissolved humic acid from water by coagulation method using polyaluminum chloride (PAC) with calcium carbonate as neutralizer and coagulant aid. Issue 2 (June 2015) - Sudoh, Ryou; Islam, Md. Saiful; Sazawa, Kazuto; Okazaki, Takuya; Hata, Noriko; Taguchi, Shigeru; Kuramitz, Hideki
Highlights Humic acid (HA) initiate growth arrest and apoptosis in fibroblasts. Positively charged HA make coagulation hard due to positively charged coagulants. We investigated HA removal using PAC with CaCO3 as neutralizer and coagulant aid. CaCO3 saves the usage of coagulants and settling time. We found that PAC is an effective coagulant for the removal of HA when using CaCO3.